Knee osteoarthritis and its related issues: patients’ perspective - Mohd Azzuan Ahmad; Devinder Kaur Ajit Singh; Chua, Wei Qing; Nor Najwatul Akmal Ab. Rahman; Fazlina@Asma Mohd Padzil (Penerbit Universiti Kebangsaan Malaysia, 2018)
Knee osteoarthritis (OA) is a common chronic joint disease that results in pain and disability in many people. Cultural practice may influence patients’ views about their condition, its related issues and management. The aim of our study was to explore the perspective about knee OA and its related issues among Malaysian patients with knee OA. Twelve patients diagnosed with knee OA (8 females and 4 males) attending physiotherapy sessions at a University Hospital, mean age (SD): 67.1(9.4) years and median visual analog scale score of 5/10 participated in this qualitative study. One to one in-depth interviews were conducted, audio recorded and later transcribed verbatim. Three main themes were identified from the transcribed data; knee pain and its’ related issues (reason and aggravating factors of knee pain, coping strategies), impact of knee pain (impact on daily activities and emotions) and physiotherapy management (effects and expectations of physiotherapy, compliance and adherence towards home exercises). Most participants expressed that their knee pain was aggravated by certain movements that had an effect on their daily activities namely squatting. The findings also suggested that physiotherapy management was perceived as secondary prevention rather than a cure. Findings from this study provides information about the perceptions and related issues of patients with knee OA. This information may help health professionals in tailoring patient-centered care and provide better management.